Disinfection of Bovine Enamel by Microwave Irradiation: Effect on the Surface Microhardness and Demineralization/Remineralization Processes - Viana, P. S. [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, E. T. [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Karger, 2010)
Enamel specimens need to be disinfected before being used in intraoral appliances and the disinfection method must not affect the integrity of the tooth. This study evaluated the effectiveness of microwave bovine enamel disinfection and its effect on the surface microhardness (SMH) and cross-sectional microhardness (CSMH) of sound, demineralized and remineralized enamel. Forty enamel specimens were divided into two groups (n = 20): control (nonirradiated) and microwave. Microwave specimens were immersed in water and irradiated (650 W/3 min). Specimens were incubated at 37 degrees C for 7 days under aerobic and anaerobic conditions. An ali-quot was removed for counting, plated at serial dilutions on blood agar plates, which were incubated aerobically and anaerobically. The colony-forming units were calculated. Other 20 enamel specimens (4 X 4 mm) were embedded in acrylic resin, polished and sliced into two halves: one of the fragments was reserved as control while the other was micro-waved. SMH and CSMH of sound enamel were analyzed for both groups. The CSMH was further evaluated after demineralization and remineralization cycles. The Knoop integral (Delta KI) was also calculated. Data were analyzed statistically by paired Student's t test (alpha = 0.05). While control specimens showed microbial growth, those microwaved were disinfected. There were no significant differences in SMH, CSMH and Delta KI between the control and microwave groups. Microwave irradiation for 3 min at 650 W was effective for the complete disinfection of bovine enamel specimens without affecting the SMH and CSMH of sound, demineralized and remineralized enamel. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Antibacterial agents; Demineralization; Disinfection; Enamel; In vitro study; Microbiology; Microhardness; Microwaves; Remineralization